0537 Symptom Improvement Reported with Some PAP Use in Non-adherent Pediatric Patients with OSA. (25th May 2022) - Scribner, April; White, Jennifer; Pruss, Kristi; Jambhekar, Supriya; Spray, Beverly
Abstract: Introduction: Positive airway pressure (PAP) is commonly used in children to treat obstructive sleep apnea (OSA) when surgery is not an option or is ineffective1-3, but adherence is often poor. Observational studies suggest utilization of PAP improves symptoms, signs, and polysomnogram indices of OSA in at least 85% of children4-9. The Agency for Healthcare Research and Quality released the report "Continuous Positive Airway Pressure Treatment for Obstructive Sleep Apnea"10. Conclusions of this report determined that the published evidence reviewed does not support that PAP affects long term outcomes. No pediatric studies were included in this report. Objectives of this study were to determine if pediatric patients with OSA who are non-adherent to PAP therapy report an improvement in symptoms with some use of PAP. Methods: A retrospective chart review was performed on patients with OSA on PAP seen in the pediatric sleep clinic. Patients were considered adherent to PAP if usage was longer than 4 hours/night for 70% of nights or more. Follow up visits occurred around 3 months, 6 months, 1 year, and 18 months-2 years. Adherence data and reported improvement in symptoms were documented at each visit, and demographical information was obtained. Results: 235 patients were included in the analysis (63.9% male, 32.3% female, 3.8% missing), with a mean age (SD) at PAP initiation of 12 years (4.5). The sample was predominately Caucasian (51.5%) or African American (38.3%), 85.9% were non-Hispanic, and 53.2% obese. The mean (SD) apnea-hypopnea index was 24.7(27.6)/hr. At first visit post-initiation, of the 138 patients that had adherence data available, 80.4% reported improvement in symptoms with PAP use. Of these patients, 55.86% were non-adherent but reported symptom improvement with some use of PAP. Visit 4 data was available for 74 patients. At visit 4, 91.9% reported improvement in symptoms. Of these, 48.53% were considered non-adherent but reported symptom improvement with some use of PAP. Conclusion: Historically, PAP adherence in children has been relatively poor11. Utilizing PAP therapy to treat OSA may result in an improvement in symptoms when used in patients who are considered non-adherent to therapy. Support (If Any):